Geochemistry of Triassic Carbonates: Exploration Guide to Pb–Zn Mineralization in North Tunisia. Issue 4 (12th September 2016) - Jemmali, Nejib; Souissi, Fouad; Carranza, Emmanuel John M.; Henchiri, Mohsen
Abstract: The Triassic carbonate rocks in Northern Tunisia (Nappes, Domes, Jurassic Mountains zones), consist of massive carbonates, clays and gypsum with authigenic minerals. These are associated with several Pb–Zn deposits and occurrences. At Jebel Ichkeul, Bechateur and Oum Edeboua, these Triassic carbonates exhibit enrichment in Pb (0.32 to 228 ppm), Zn (17 to 261 ppm), Cd (5 to 6 ppm) and Co (0.3 to 89.5 ppm), with respect to their average contents in crustal carbonates. The enrichment is more pronounced at Oum Edeboua (near the ore zone). Permeability is one of the most effective factors of dispersion of metallic trace elements, causing the development of geochemical halos. The genetic relationship of the Triassic carbonate rocks with the ore deposits was controlled by diapirism and tectonic movements, which favored mineralization along the Triassic‐cover contact as well as the remobilization of metals from the mineralized rocks. Analysis of metallic trace elements in Triassic rocks provides clues to the presence of possible mineral deposits. These could be effectively used for both geochemical interpretation and mineral exploration. Carbon and O‐isotope data (– 9.3‰ <  δ 13 C < +3‰; +21.9 < δ 18 O < +31‰) suggest that the Triassic carbonates of all study areas have marine carbonates as their origin; some of them show significantly lower δ 18 O values indicating some exchange with hydrothermal fluids. Calcites associated with mineralization at Oum Edeboua have δ 13 C of –6.2‰ to –8.22‰ and δ 18 O of +24.88‰ to +25‰. The C‐isotope compositions of these calcites are 13 C depleted, indicating an organic origin. Abstract : Metallic trace elements, normalized to mean trace metal concentrations in crustal carbonates (Rose et al ., 1979), in samples of Triassic carbonates at Bechateur, Jebel Ichkeul, Jalta, Oum Edeboua and Jebel Ressas.